2020
DOI: 10.1093/ndt/gfaa059
|View full text |Cite
|
Sign up to set email alerts
|

Young adults have worse kidney transplant outcomes than other age groups

Abstract: Background The objective of this study was to establish if renal transplant outcomes (graft and patient survival) for young adults in England were worse than for other age groups. Methods Outcomes for all renal transplant recipients in England (n = 26 874) were collected from Hospital Episode Statistics and the Office for National Statistics databases over 12 years. Graft and patient outcomes, follow-up and admissions were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In concordance with other studies, we found that adolescents and young adults have worse graft outcomes than other age groups, 11 , 29 verified by the 5-y survival rate that was significantly lower in the youngest group (<26-y; 89% versus 26–50 y; 94% [ P = 0.01]). Another study has also found the time period around the transition to adult-oriented care to be a high-risk period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concordance with other studies, we found that adolescents and young adults have worse graft outcomes than other age groups, 11 , 29 verified by the 5-y survival rate that was significantly lower in the youngest group (<26-y; 89% versus 26–50 y; 94% [ P = 0.01]). Another study has also found the time period around the transition to adult-oriented care to be a high-risk period.…”
Section: Discussionsupporting
confidence: 92%
“…34 Hooper et al implemented an adherence promotion system at their center in which they approached the patients' barriers to medication adherence in conjunction with a designated clinical team and demonstrated a 50% reduction of allograft acute rejection. 35 In concordance with other studies, we found that adolescents and young adults have worse graft outcomes than other age groups, 11,29 verified by the 5-y survival rate that was significantly lower in the youngest group (<26-y; 89% versus 26-50 y; 94% [P = 0.01]). Another study has also found the time period around the transition to adult-oriented care to be a high-risk period.…”
Section: Discussionsupporting
confidence: 91%
“…A recipient age ≥ 60 years is a risk factor for one-year eGFR decline, and affects the five-year eGFR by lowering one-year eGFR [ 10 ]. In addition, previous studies have demonstrated that renal allograft survival is the worst in young recipients between 10 and 20 years of age [ 33 , 34 ]. It should also be noted that the proposed network showed that the recipient age < 29 years was associated with high eGFR at discharge, whereas the recipient age > 57 years was related to low eGFR at discharge ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Care within ethnic minority groups [10] can be difficult with patients being on the waiting list [11] for longer periods of time due to a shortage of organs from suitably appropriate ethnic minority donors, there may be other barriers such as language, cultural or misunderstanding of service [12] care pathways [13]. Some evidence suggests that young adults may have worse outcomes [14]. Many UK transplant centres currently provide restricted access due to COVID-19 [15].…”
Section: Introductionmentioning
confidence: 99%